Semantic technology : 7th Joint International Conference, JIST 2017, Gold Coast, QLD, Australia, November 10-12, 2017, proceedings /: 7th Joint International Conference, JIST 2017, Gold Coast, QLD, Australia, November 10-12, 2017, proceedings. (2017) - Unknown
No abstract available